Relationship between Family Health Behavior with Improving Patient Functional Capacity Post Stroke in the Dwikora Area - Ristika Julianty Singarimbun (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
Stroke is the biggest disease that causes paralysis of the limbs. Stroke patients require comprehensive treatment, including long-term recovery and rehabilitation efforts, even for the rest of the patient's life. The family plays an important role in this recovery phase, so from the start of treatment the family is expected to be involved in patient care. Family knowledge in the care of post-stroke patients is very important to be able accelerate the independence of post-stroke patients. This study aims to analyze the relationship between family health behavior and increasing the functional capacity of post-stroke patients in the Dwikora Area. The research was conducted in October 2021 - February 2022 the type of research is cross sectional. The study population was a family of post-stroke patients, totaling 30 people. The sampling technique used total sampling. Data collection in the study was carried out by distributing questionnaires directly to families. The statistical test used is the spearman rank. Based on the results of research conducted in the Dwikora Region, the majority of family knowledge in increasing the functional capacity of post-stroke patients was sufficient, 15 people 56.7%, both 13 people 43.3% and less than 2 people 6.7%. The attitude of the family in increasing functional capacity after stroke was a good majority of 15 people 50%, quite a number of 11 people 36.7% and less a number of 4 people 13.3%. Family action in increasing unctional capacity after stroke is sufficient for the majority of 17 people 56.7%, good for 11 people 36.7% and less for 2 people 6.7%, It is hoped that the family will carry out its role by increasing knowledge, attitudes and actions, so that the patient can independently carry out his own activities.